Evaluation of the gravitational effects on flow boiling heat transfer of R134a in a 0.5 mm tube under conditions of imposed wall-temperature - Filho, Erivelto dos Santos; Leão, Hugo Leonardo Souza Lara; Cardoso, Elaine Maria [UNESP]; Ribatski, Gherhardt (Taylor & Francis, 2023)
This paper presents an experimental investigation of heat transfer coefficient and dryout inception during flow boiling of R134a in a circular channel with an internal diameter of 500 (Formula presented.) for horizontal, 45° inclined, and vertical upward flows. The microchannel was heated by imposing the wall temperature by flowing hot water counter-currently to the test fluid through an annular region containing the test section. Experiments were performed for mass velocities ranging from 350 to 600 kg/(s·m2), heat fluxes up to 46 kW/m2, saturation temperature of 30 °C, and vapor qualities from 0 to 1. The experimental data were parametrically analyzed, and the effects of the experimental parameters (heating method, mass velocity, heat flux, and channel orientation) were identified. Almost similar heat transfer behaviors were found under conditions of imposing wall temperature and heat flux through the Joule effect. The effect of the flow orientation on the heat transfer coefficient prior to the dryout inception was negligible. The heat transfer coefficient increases with increasing vapor quality, heat flux, and mass velocity. The critical heat flux exhibited similar values independently of the flow orientation. Moreover, the critical heat fluxes increases as the dryout inception vapor quality reduces, regardless of the flow orientation.